PROSES PENYUSUNAN ANGGARAN UNTUK MEWUJUDKAN KINERJA DAN KEPUASAN KERJA BERBASIS PARTISIPASI DI UNIVERSITAS TEUKU UMAR - Ferawilyanti, Ferawilyanti; Supriono, Bambang; Rozikin, Mochammad (Profit: Jurnal Adminsitrasi Bisnis, 2019)
Higher education prioritizes quality in achieving the vision and mission, achieving the vision and mission is strongly influenced by the strength of the budget owned by a college. The strength of the budget is not only seen from how much the existing budget is, but also how the wisest way to manage the budget. This research is motivated by the limited budget owned by a new state university in managing the budget in a participatory manner in achieving the university's vision and mission. For this reason, a participatory system is needed for the budgeting process, starting from the planning stage, the process, accountability and results that lead to the university's vision and mission. The study was conducted to obtain information on whether participatory budgeting has an influence on employee performance, whether participatory budgeting also has an impact on employee job satisfaction at Teuku Umar University, also seeing whether there is an effect of employee job satisfaction on employee performance. This study also wants to find out whether there is an influence of motivation on employee performance, the influence of participatory budget on employee performance through motivation, and whether employee job satisfaction affects employee performance through motivation.